Evaluation of α-Alumina Nanoparticles Prepared by Sol-Gel Method - Razzaq, Farah M. Abdul; Jabur, Adnan S. (Basrah Journal for Engineering Sciences, 2024)
Nanoparticles show mechanical, electrical, chemical and optical properties that are different and superior to bulk materials. In the present work, α-Alumina nanoparticles were synthesized using the nonorganic Sol-Gel method under controlled conditions. Because of the low cost of its raw materials, low manufacturing temperature and the high purity of the product, Sol-Gel method is the best in the manufacture of nanostructures like metal oxide nanoparticles. The precursor of the Sol-Gel process was aluminum nitrate with ethanol. The prepared nanopowder was evaluated by X-ray diffraction (XRD), scanning electron microscope (SEM), electron dispersive spectroscope (EDS) and Malvern Zetasize analyzer.